Predicting the Anti-Tuberculosis Mechanism of Vitex cofassus Methanolic Extracts through Network Pharmacology Analysis: Prediksi Mekanisme Antituberkulosis Ekstrak Metanol Vitex cofassus melalui Analisis Farmakologi Jejaring - Sri Wahyuli Astian Omir; Ruslin Ruslin; Muhammad Arba (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2026)
asasas